Case reportPsychotic manifestations as an initial presentation in glioma: two case reports and review of literature - Singh, Daleep; Kapoor, Akhil; Khadda, Sandeep; Singhal, Mukesh Kumar; Singh, Guman; Bagri, Puneet Kumar; Kumar, Harvindra Singh (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2014)
Psychotic manifestation as an initial presentation of brain tumor is a rare manifestation of the primary disease. A 32-year-old male patient presented with auditory and visual hallucinations, delusion of persecution and profound agitation. The patient was initially suspected as a case of acute psychosis; however, on imaging work-up, a large central space-occupying lesion (SOL) in the brain was detected. Following surgical removal of the brain tumor, psychotic manifestations disappeared. The pathology revealed astrocytoma grade III. Similar presentation was observed in a 28-year-old woman who first visited the psychiatry department. Imaging revealed an SOL in the right parietal lobe. She underwent craniotomy and gross total resection of the tumor. The histopathology of the surgical specimen revealed astrocytoma grade II. Neuropsychiatric manifestations may have a large impact on the quality of life of patients with primary brain tumors and should therefore be adequately managed.